Innovative potential of small-sized enterprises in Kazakhstan, key problems, ways and criteria for development - Bayadilova, B.M.; Orynbekova, G.A.; Koichubayev А.S. (BUKETOV BUSINESS REVIEW, 2019)
One of the main aims of this article is to substantiate the role and importance of the development of the innovative potential of small and medium-sized entrepreneurship within the conditions of increasing the number and frequency of various ethnic and social conflicts and during the transition of modern society to a new technological structure. The article provides a study of the concept of «innovation potential» of small enterprises and considers approaches to research this sphere. In the course of the study, it was revealed that a thing that the considered approaches have in common is the attitude towards disclosure of notion of «innovative potential» through the study of its components «potential» and «innovation». Nevertheless, differences arise when choosing the methodological essence of the concept. The author’s own definition of the concept of «innovation potential» was invented, applicable to small business forms as the abilities of the management and employee teams of such enterprises using available resources to create innovations in the relevant industry as fast as possible, also to quickly adapt to changes in the market in conditions of uncertainty, high risk and multi-factor external environment. The main directions and features of the development of the countries’ innovative potential of small-sized enterprises were investigated, the investigation included such criteria as the small number of employees, the efficiency of the innovation process, the presence of an innovative engineer, the innovative activity of employees, the diversification of innovation actions, the need to actively search for new ideas, the utilization of the whole country’s infrastructure potential and the social direction of innovation activities. In conclusion of the article, brief description of the main problems of the development of innovative entrepreneurship in the East Kazakhstan region and an analysis of the current state of affairs in the field of innovation development are provided. The analysis showed that, despite the presence of very large barriers in the maximum utilization of the innovative potential of small businesses both in the country and in the region, the opportunities for this are present and this will increase the effectiveness of small business participation in the processes of economic modernization.